Performance of female teachers employed in education center in Rasht city ‎regarding prevention of osteoporosis and their attitude on the role of mass media - shadman reza masouleh; masoumeh jafari asl; moohamadali yazdani (Journal of Holistic Nursing and Midwifery)
Introduction: Osteoporosis is a silent disease that can cause decreased bone mass and put it at ‎risk of fracture. Therefore prevention at younger age can prevent its consequences.‎